Stability of milk and gliadin on swabs during 7 days under different storage conditions. (April 2020) - Barrere, Virginie; Théolier, Jérémie; Lacroix, Sébastien; Zbylut, Steven; Valdez, Alexcia; Collopy, Nick; Lahey, Brandon; Godefroy, Samuel
Abstract: Food industries rely on swabbing to control allergen and gluten occurrences in their manufacturing plant. However, collecting allergens from a surface with a swab and further analysis can be affected by numerous aspects, like the operator, the allergen, the swab fabric, the ELISA kit, and the procedure. In addition, food companies often send swabs to external laboratories, but there are no available data to describe the effect of time and temperature on the allergen or gluten stability on the swabs. This study presents the stability of milk and gliadin collected from a stainless-steel surface using different swab types (cotton, Dacron, rayon, polyester, and polyurethane). The protein concentrations were tested on days 0, 1, 2, 3, and 7 by an ELISA technique to follow the protein concentration over time. The swabs with gliadin were stored at 37 °C for 7 days to mimic poor storage conditions. The swabs used to collect milk were stored at 4 and 37 °C. The experiments indicated that, except for two cases, there was no difference in gliadin concentrations between day 1 and the other days; the same observation was made for milk. However, the swab types were not equivalent and some led to false-negative results. Validation of those observations was undertaken at a commercial laboratory. To reduce the risk of false-negatives and the effect of factors influencing the result (operator, swab, procedure, and allergen), it is recommended to swab an area in triplicate. Highlights: Validation and monitoring of allergen cleaning program rely on the detection method. Swab fabric, operator, and procedure affect milk and gliadin recovery from a surface. Milk and gliadin are stable on swabs during 7 days storage and detectable by ELISA. Swab triplicates per testing area would decrease the risk of false negatives.